Intravenous immunoglobulin for prophylaxis of neonatal sepsis in premature infants. Issue 4 (April 1988) - Stabile, A; Miceli Sopo, S; Romanelli, V; Pastore, M; Pesaresi, M A
Abstract : The incidence of sepsis, mortality due to sepsis, total mortality, and minor infections was evaluated in a group of 46 premature newborn infants who were treated with intravenous immunoglobulins. They were compared with an untreated control group. No significant differences were observed between the two groups.